Legal Protection of Tangible Cultural Properties from the Consequences of Environmental Pollution - Batrićević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
Cultural properties are considered as artificially created environmental values or environmental values created by human labor and are extremely susceptible to the destructive impacts of negative anthropogenic factors directed towards different eco mediums such as air, water and soil. Legal protection of cultural properties from pollution is closely related to the protection of the environment in general and is accomplished on several levels: international and national, criminal legal and administrative, legal and sublegal, within environmental legislation and within other branches of law. Accordingly, the subject of this paper includes the discussion of legal frameworks of direct and indirect importance for the protection of cultural properties from pollution on a global level as well as within the borders of the Republic of Serbia. Moreover, some weaknesses of existing national solutions have been pointed out in order to initiate their possible alterations and improvements in accordance with world trends regarding environmental protection and protection of cultural heritage, as well as with obligations derived from ratified international documents and the Process of European Integration.